(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
What is the role of movies and cartoons in the process of general secondary education? How do students react? The educational value of cartoons…. We all know that the educational process and the role of education in it, the relationship between teacher and student, parent-child-school-education are all interrelated and one of the most pressing issues today. Why exactly cartoons, in this article we will look at exactly these issues. In this process, the importance of various fairy tales of our grandparents, beginning with "Once upon a time,..." from childhood, is very important for all of us. We have all become friends with fairy-tale heroes, sometimes imagining ourselves in their place. We dreamed of living in a fairy-tale world rather than real life. Because listening to them awakens in the human heart a feeling of boundless love for the mother earth, pride in its history, boundless pride, hidden like fairy-tale heroes, masculinity. The struggle against evil awakens a sense of good in those who have evil intentions. Cartoons based on these fairy tales and loved by all children, express the spiritual feelings and heroism of the people, their courage, true love and devotion to the Motherland, and strengthen the innocence in the heart. Cartoons shape children’s worldviews and show that people should be friends and care for each other, and fight against oppression and injustice with unity. From an early age, this genre of cinema left a deep and immortal impression, giving rise to the first notions of good and evil. The child sees the work based on a fairy tale with a different eye, notices what he does not hear when he hears or reads.